Botanical Origin and Biological Properties of Honey and Propolis from Cuautitlan, State of Mexico, Mexico - Jose Juan Alcivar-Saldaña; Marco Aurelio Rodriguez-Monroy; Liborio Carrillo-Miranda; Maria Margarita Canales-Martinez (MDPI AG, 2024)
Beekeeping is an activity that generates various products, mainly honey and propolis, with different biological activities that are studied extensively using various methodologies. The influence of various phenolic compounds, such as phenols and flavonoids, which are synthesized and concentrated differently in each product depending on the melliferous flora and sources of resources, on the manufacture of propolis or honey has been investigated. However, the analysis of these products has been performed separately and is outdated in time, and depending on the area and the flowering periods, different crops may be harvested. The analysis of the honey and propolis produced in Cuautitlan, State of Mexico, in the high plateau beekeeping zone, for a period of four years, both in the dry and rainy seasons, was proposed to determine the botanical origin of the honey and propolis. The primary pollen type in both honey and propolis was from Brassica rapa. Physicochemical tests were conducted, revealing higher concentrations of antimicrobial activity in the dry season than in the rainy season. Honey, propolis, and a vegetation extract showed activity against S. aureus, while only honey had an effect on E. coli in both seasons. For antifungal activity, only propolis collected in the rainy season had this activity. The biological properties of these products are closely related to the flora that varies both annually and between seasons, influencing the concentrations of phenolic compounds, as well as the biological activity of honey and propolis.